Measuring The Effectiveness of Private Electronic System Organizers Regulations In Developing Social Media Equilibrium - Sitabuana, Tundjung Herning; Adhari, Ade; Suryani, Leony Sondang; Sanjaya, Dixon; Amri, Ibra Fulenzi (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2023)
Technological developments, especially social media, potentially have a negative impact that pretend to social disintegration and instability. To prevent and create a healthy and conducive digital space, the Government issued the Minister of Communication and Information Regulation No.5/2020 concerning Private ESOs. This regulation gives the government authority to supervise Private ESOs and protect social media content. This research aims to examine ministerial regulation effectiveness in realizing social media equilibrium and its impact on digital democracy in Indonesia. This is a sociolegal research. The data was obtained from observation, expert interviews, and literature studies which were analyzed qualitatively. Normatively, restrictions and supervision to the right to use social media through private ESOs can be carried out to be in line with Pancasila’s Spirit. However, there are fundamental errors in ministerial regulation: (1) multiple interpretations norm; (2) unclear parameters of supervision; and (3) weak legal position of ministerial regulations in law enforcement. Sociologically, the presence of ministerial regulations is weak and ineffective because they are: (1) rejected by stakeholders; (2) easy to change; and (3) slowly responded in socialization process and community compliance. More comprehensive implementation regulation is required with, supervision through an electronic system approach to increase the role and participation of community.